2007
DOI: 10.1111/j.1365-2745.2007.01262.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem engineering facilitates invasions by exotic plants in high‐Andean ecosystems

Abstract: Summary1 Ecosystem engineers are organisms that change abiotic conditions in ways that affect the performance and distribution of other species, including exotics. Several mechanisms have been proposed for the successful establishment of exotic plants in natural communities, but the positive effects that native engineer species may have on the distribution and performance of exotic plants remain unknown. 2 In this study, we propose that amelioration of extreme abiotic conditions by ecosystem engineers can make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
77
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 55 publications
11
77
0
2
Order By: Relevance
“…For instance, Azorella madreporica, a Chilean cushion species, was found to display both positive and negative associations with plant species depending on the plants location outside or inside the cushion vegetation (Fajardo et al 2008). Plant interactions associated with cushions and environmental gradients supports the stress gradient hypothesis (Bertness and Callaway 1994) showing that the frequency of facilitation increases with environmental severity (Smith et al 1995, Badano et al 2007, Cavieres and Badano 2009). Studies on the biology of cushions have also generated a substantial body of literature (32 publications) including research on life history (7), genetics (9), reproduction (10), and evolution (6).…”
Section: The Ecological Significance Of Cushions Plants: Heavy or Ligmentioning
confidence: 93%
“…For instance, Azorella madreporica, a Chilean cushion species, was found to display both positive and negative associations with plant species depending on the plants location outside or inside the cushion vegetation (Fajardo et al 2008). Plant interactions associated with cushions and environmental gradients supports the stress gradient hypothesis (Bertness and Callaway 1994) showing that the frequency of facilitation increases with environmental severity (Smith et al 1995, Badano et al 2007, Cavieres and Badano 2009). Studies on the biology of cushions have also generated a substantial body of literature (32 publications) including research on life history (7), genetics (9), reproduction (10), and evolution (6).…”
Section: The Ecological Significance Of Cushions Plants: Heavy or Ligmentioning
confidence: 93%
“…and Cerastium arvense L. (e.g. Cavieres et al 2005Cavieres et al , 2007Badano et al 2007). Probably life-forms of contrasting architectures (i.e.…”
Section: Plant Scalementioning
confidence: 99%
“…Secondly, if cows are efficient vectors, the seeds can be transported beyond the current invasion front of this exotic plants (2200 masl) to the cushion plants zone (Laretia acaulis, Azorella monantha and Azorella madreporica) which range from 2800 to 3400 masl (Armesto et al 1980); this seed movement is plausible as we have observed horses feces above 3000 masl and beyond. It is well documented that cushion plants provide microclimate conditions for exotic plants, which increase growth, survival and reproduction on species such as Taraxacum officinale and Cerastium arvensis , Badano et al 2007, Arredondo et al 2009). Therefore, it is probable that this positive interaction might occur with Eschscholzia californica as well.…”
Section: Discussionmentioning
confidence: 99%